Prejudice against psychiatry - Aleksandra Iwona Zimna; Hubert Wróblewski (Kazimierz Wielki University, 2021)
Introduction: There are many stereotypes in society about psychiatric patients and the diseases they suffer from. Psychiatrists themselves are often treated with reserve by society. They cause respect among patients and, at the same time, fear of having to visit. Aim of the study: The aim of the study is to analyze the attitude of society to psychiatric patients, their diseases and psychiatrists. Methods: The results of the study were obtained on the basis of an online survey. Results: 138 respondents took part in the survey, 81.2% were women and 18.8% were men. As many as 22% of respondents do not know who a psychiatrist is, confusing his competence with a psychologist. Over 40% believe that they would feel more stressed before visiting this doctor than with any other specialist, 31.9% associate visiting a psychiatrist with decreased self-esteem, difficulty in finding a permanent job (21%) and perceive them as embarrassing (70 %) More than half of the respondents admit that they would conceal this fact from the employer. As many as 62.3% of the respondents would not enter into a partnership with a person receiving treatment from a psychiatrist. Conclusions: On the basis of the obtained results, it can be noticed that the society is prejudiced against psychiatric patients, diseases in this field and specialist doctors themselves. Fear, insecurity, and withdrawal can be conditioned by an inadequate level of knowledge. However, as the years go by, society's confidence in psychiatrists is growing, to comfort.